Optimasi Frekuensi Kontrol pada Sistem Hybrid Wind-Diesel Menggunakan PID Kontroler Berbasis ACO dan MFA - Arrohman, Muhammad; Fajardika, Risky; Muhlasin, Muhlasin; Ali, Machrus (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
The power of the generating system is strongly influenced by frequency changes. The wind generating system is strongly influenced by the magnitude and speed of the agin as input power. The wind-diesel combined generating system is required to obtain optimum power quality. The hybrid swarm system is a controlled network of some renewable energy generation such as: wind turbine, solar cell, micro hydro and so on. Not optimal setting gain and small constant time on Load Frequency Control (LFC), causing its ability to be weak (weak line). In practice, wind-diesel systems are controlled with PID controller. Setting the gain value of the PID is still in the conventional method, making it difficult to get the optimal value. In this research applied control design by using Intelligent Method in finding the optimum value of Proportional Intergral Derivative (PID) to adjust load frequency with Matlab / Simulink program. This research uses Ant Colony Optimization (ACO) and Modification Firefly Algorithm (MFA). For comparison methods are used without control method, conventional PID method and matlab auto tuning method. Wind-diesel modeling uses the transfer function of diagram of wind turbine and diesel. The study compared several uncontrolled methods and conventional PID, ACO, with FA and MFA. The results show that the smallest undershoot is PID-MFA Controller of -1.529.10-4 and the fastest settling time on the PID-ACO controller 11.5 seconds